Identification of the critical activity in heat treatment process using TISM. (2021) - Bathrinath, S.; Koshy, Roopa Ann; Bhalaji, R.K.A.; Koppiahraj, K.
Abstract: The heat treatment process (HTP) is crucial in the manufacturing of any component, also the activities concerned with the heat treatment process are often subject to hazards. When the data related to industrial accidents are analyzed, it is identified that most of the industrial accidents have occurred because of HTP. Considering this, this research work intends to identify, analyze, and prioritize the activities carried in the HTP based on the nature of hazards. To identify the various activities carried out in the HTP and to understand the nature of hazards involved, a study was carried out in gear manufacturing company located in western Tamilnadu, India. Eighteen activities carried in the HTP are identified. Then, the total interpretive structural modeling (TISM) method is used to analyze the various activities. In the TISM method, the obtained results are generally arranged in hierarchical order, and the activity at the bottom of the hierarchy need to be addressed immediately. Next, MICMAC analysis is performed to understand the relationship between the activities. In our case, the activating finishing process, tempering, vacuum hardening process, and nitriding case hardening process are at the bottom level, and these activities need to be addressed in a short time. In MICMAC analysis, out of the 18 activities, 4 comes under the autonomous category, 3 comes under the dependent category, 6 comes under the linkage category, and 5 comes under the independent category. Based on the results obtained, some practical managerial implications are suggested for the mangers and practitioners involved in the heat treatment process.